Structural change and environmental impact - Martin Jänicke; Harald Mönch; Thomas Ranneberg; Udo E. Simonis (Intereconomics, 1989)
Although structural change in many industrialized countries has increased since the early 1970s, the environmental policy aspects of this change have hardly been investigated. Using a set of four indicators, this study examines the correlation between structural changes and environmental pollution in thirty-one Eastern and Western industrialized countries from 1970 to 1985.
Keywords: 330; Environmental Policy